The Use of Authentic Reading Materials (ARMs) to Develop Students’ Vocabulary - Rifqah Rifqah; Fitri Radhiyani; Muhammad Miftah Fauzan (State University of Makassar, 2026)
Vocabulary development is essential for English language learners, yet many junior high school students struggle with limited vocabulary due to unengaging instructional resources. This research aims to explore the effectiveness of Authentic Reading Materials (ARMs) in developing the vocabulary of eighth-grade students at SMP Aisyiyah Sungguminasa. This research employed a quantitative pre-experimental design with a one-group pretest-posttest approach. The researcher selected 26 students using cluster random sampling and collected data through vocabulary tests administered before and after the treatment. The intervention involved real-world texts such as brochures, signs, posters, and inspirational quotes to present vocabulary in context. The data were analyzed using descriptive statistics and the Wilcoxon Signed-Rank Test via SPSS. The findings revealed a significant improvement in students’ vocabulary, with the mean score increasing from 42.12 in the pre-test to 63.27 in the post-test. Statistical analysis confirmed this growth with a significance value (p) of < .001. Consequently, this research concludes that ARMs effectively enhance vocabulary development by providing real-life contexts that aid retention. These materials serve as a practical and motivating alternative to traditional memorization methods for junior high school students.Keywords: authentic reading materials, EFL, real-life communication, secondary school, vocabulary development